Applying a Genre Based Approach to Teaching Writing a Recount Text A case study at a Junior High School in Bandung - Nurhayati, Delis Tati (2014)
This study applied a Genre-Based Approach to teaching writing a Recount text at a Junior High School level in Bandung. The study was designed to address two research questions: (1) How can the activities at each the stage of the GBA help students improve their writing ability? (2) What are the students' difficulties to write a Recount text? The study employed a qualitative case study, and the data were obtained by using classroom observations, analyses of students' texts, and interviews (Creswell, 2003, p.185). Classroom observations were conducted in twelve meetings to investigate the activities at each stage of the Genre-Based Approach. Analyses of students' texts were done to investigate whether the texts were able to achieve their social function. Interviews with the students were conducted to find out students' opinions of the activities at each stage of the GBA as well as to identify students' difficulties when they wrote the text. The data from classroom observation, analyses of students' texts, and interviews were used to answer the research questions. The findings revealed that the activities at each stage of the GBA could help students improve their writing ability. Firstly, the activities at the stage of Building Knowledge included reading some references to learn the topic; learning new vocabulary from the text and having an Excursion. These activities could help students improve their background knowledge about the topic to write. Secondly, the activities at the stage of Modeling included learning Generic Structure, Language Feature, relevant grammar and vocabulary. These activities helped students increase their knowledge about the Generic Structure, Language Feature, relevant grammar and vocabulary to write a Recount text. Thirdly, the activities at the stage of Joint Construction included preparing a Recount Plan and drafting; and finally the activities at the stage of Independent Construction involved preparing a Recount Plan and drafting; teacher's feedback to revise the text and publishing. These activities helped students how to write a successful Recount text. Therefore, it is concluded that the activities at each stage of the GBA can help students improve their writing ability. The improvement could be seen from the Independent Recount texts which indicated their control of the Schematic Structure and Linguistic Features of a Recount text. Regarding the students' difficulties, from their diagnostic texts, it was found that some students had some problems in using word choice and relevant grammar such as sentence and paragraph arrangements. However, after applying the Genre Based Approach the students' difficulties could be solved. Therefore, it is suggested that the activities at each stage of the Genre Based Approach ca